2008
DOI: 10.1177/0883073807313047
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Functional Magnetic Resonance Imaging (fMRI): Issues and Applications

Abstract: Functional magnetic resonance imaging (fMRI) represents a useful tool for studying brain functions and the neural basis of cognition in healthy children and in those in disease states. Functional magnetic resonance imaging is a relatively new use of existing magnetic resonance imaging technology that allows scientists and practitioners to observe the brain at work. It is based on the observation that local increases in blood flow are related to neural activity. This review considers principles of functional ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 83 publications
2
45
0
1
Order By: Relevance
“…From a clinical perspective, it is considered that fMRI may replace or serve as an important adjunct to the invasive intracarotid amobarbital (Wada test) or direct cortical stimulation mapping procedures, in order to delineate the eloquent cortex to be spared in children who are candidates for surgical resection (O'Shaughnessy et al, 2008). In line with studies showing the utility of presurgical fMRI language mapping in adults (Binder et al, 1996;Gaillard et al, 2002;Roux et al, 2003;Rutten et al, 2002;Tie et al, 2008Tie et al, , 2009, studies have reported the potential utility of this procedure in the even more crucial context of childhood (Anderson et al, 2006;Gaillard et al, 2000Gaillard et al, , 2001bHertz-Pannier et al, 1997;Holland et al, 2001;Wilke et al, 2005Wilke et al, , 2006.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…From a clinical perspective, it is considered that fMRI may replace or serve as an important adjunct to the invasive intracarotid amobarbital (Wada test) or direct cortical stimulation mapping procedures, in order to delineate the eloquent cortex to be spared in children who are candidates for surgical resection (O'Shaughnessy et al, 2008). In line with studies showing the utility of presurgical fMRI language mapping in adults (Binder et al, 1996;Gaillard et al, 2002;Roux et al, 2003;Rutten et al, 2002;Tie et al, 2008Tie et al, , 2009, studies have reported the potential utility of this procedure in the even more crucial context of childhood (Anderson et al, 2006;Gaillard et al, 2000Gaillard et al, , 2001bHertz-Pannier et al, 1997;Holland et al, 2001;Wilke et al, 2005Wilke et al, , 2006.…”
Section: Introductionmentioning
confidence: 96%
“…In the context of pediatric fMRI, another major issue is that many language paradigms shown to be useful in adult studies are not well suited for children, and that child-specific tasks have to be specially designed (O'Shaughnessy et al, 2008;Wilke et al, 2003aWilke et al, , 2006. This may be even more problematic for children suffering from neurological or developmental disorders, especially language disorders.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…It should first be noted that there are specific aspects to performing fMRI studies in children. On one hand, fMRI even in healthy children already poses a number of special challenges: from a child-friendly task design and extensive subject preparation to pediatric particularities during data processing, great care must be taken to appropriately account for the special needs of children [O'Shaughnessy et al, 2008;Wilke et al, 2002Wilke et al, , 2008. This is all the more true for children with a neurological disorder like epilepsy: both the disorder itself and the necessary medication may influence the child's ability to cooperate [Yerys et al, 2009].…”
Section: Discussionmentioning
confidence: 98%